Penyuluhan Tentang Pengelolaan Bisnis Pada UMKM di Desa Kalikidang, Kecamatan Sokaraja, Kabupaten Banyumas, Jawa Tengah - Setyawati, Irma; Dewi, Dyah Handayani; Amalia, Bela; Sekarani, Shalsyadila Safira; Azizah, Fadilla Nur; Dharmawan, Rifky; Ramadhan, Abdul Fathir; Rinaldi , Dwiningtyas (Jurnal Pengabdian kepada Masyarakat UBJ, 2024)
The purpose of community service activities in Kalikidang Village is to provide counseling to MSMEs about business management so that MSMEs are able to become pillars of the Indonesian economy, contribute to the GRDP of Banyumas Regency and are able to absorb labor. This community service activity uses counseling methods to present material from resource persons to the audience, in addition, the practice of creating branding and marketplaces to increase online sales and marketing is carried out. The service activity is said to be successful, because it can increase knowledge and understanding of branding and marketplace around 80% of MSME actors in Kalikidang Village. The MSME actors of Kalikidang Village were very enthusiastic in listening to the explanations from the resource persons, and gave a positive response to student assistance. Thus, MSME players have a strong desire to create branding with the aim of increasing sales through online marketing. To increase the knowledge and understanding of MSME actors about branding and marketplaces, the Village Head and his staff should need to increase soft skills activities to increase the understanding and skills of MSME actors in managing their business will later help MSMEs in entering the world of competition, both nationally and globally